Pengaruh Product Diversity dan Restaurant Atmosphere terhadap Loyalitas melalui Kepuasan Konsumen pada Rumah Makan Pemancingan Suharno 2 di Kabupaten Semarang - Prakosa, Eirene Arella Welove Firsta; Abidin, Zainal (Fakultas Perikanan Universitas Pekalongan, 2025)
Semarang Regency, especially Bandungan Subdistrict, is known as a tourist destination with growing culinary potential. Tight competition in the culinary business requires businesses to understand the factors that influence customer satisfaction and loyalty. This study aims to analyze the effect of product diversity and restaurant atmosphere on customer loyalty, either directly or through customer satisfaction as a mediating variable. The research was conducted at Pemancingan Suharno 2 Restaurant from December 2024 to January 2025 using a descriptive quantitative approach. A sample of 119 respondents was obtained through purposive sampling technique, with the criteria that customers are at least 17 years old and have made purchases at least twice in the last year. Data processing was carried out using SEM analysis with the help of WarpPLS 7.0 software. The results showed that product diversity and restaurant atmosphere have a positive and significant effect on customer satisfaction and customer loyalty. In addition, restaurant atmosphere has a significant indirect effect on customer loyalty through customer satisfaction, while product diversity does not show a significant mediating effect. These findings confirm the importance of creating a supportive restaurant atmosphere and relevant product diversity to increase customer satisfaction and loyalty.